ECCO Position Paper : harmonization of the approach to ulcerative colitis histopathology - Magro, Fernando; Doherty, Glen; Peyrin-Biroulet, Laurent; Svrcek, Magali; Borralho Nunes, Paula; Walsh, Alissa; Carneiro, Fatima; Rosini, Francesca; de Hertogh, Gert; Biedermann, Luc; Pouillon, Lieven; Scharl, Michael; et al. (Journal of Crohn's and colitis, 2020)
© The Author(s) 2020. Published by Oxford University Press on behalf of European Crohn’s and Colitis Organisation. All rights reserved. This article is published and distributed under the terms of the Oxford University Press, Standard Journals Publication Model (https://academic.oup.com/journals/pages/open_access/funder_policies/chorus/standard_publication_model). Currently, the main targets of drug therapy for ulcerative colitis [UC] are endoscopic and clinical remission. However, there is active discussion about the additional advantages of including histological remission as a target. Accumulating evidence indicates that microscopic activity persists in endoscopically quiescent UC, that histological changes may lag behind clinical remission after treatment, and that absence of histological activity predicts lower rates of relapse, hospitalization, surgery and subsequent neoplasia. Obtaining useful information from mucosal biopsies in this setting depends on accurate and consistent evaluation of histological features. However, there is no standardization of biopsy procedures, histological sample processing technique or histological scoring systems, and there is no agreement on the definitions of histological remission, response or activity. Accordingly, a consensus expert panel convened by the European Crohn's and Colitis Organisation [ECCO] reviewed the literature and agreed a number of position statements regarding harmonization of UC histopathology. The objective was to provide evidence-based guidance for the standardization and harmonization of procedures, definitions and scoring systems for histology in UC, and to reach expert consensus where possible. We propose the absence of intraepithelial neutrophils, erosion and ulceration as a minimum requirement for the definition of histological remission. For randomized control trials we recommend the use of the Robarts histopathology index [RHI] or the Nancy index [NI]. For observational studies or in clinical practice we recommend the use of the NI. To predict the risk of future neoplasia in UC, cumulative histological scores over time are more useful than single scores.